PENGARUH PEMBERIAN KOMPRES JAHE MERAH TERHADAP PENURUNAN SKALA NYERI PADA PENDERITA GOUT ARTHIRITIS DI RS HORAS INSANI - Sinaga, Eka Malini; Seriga Banjarnahor (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Gout is usually characterized by hyperuricemia (increased uric acid levels in the blood) and is characterized by rheumatic pain in the joints, pain, tenderness, redness and swelling. This condition is known as gout. Gout is a disease that can be controlled even if it is not cured, but if left alone, this condition can develop into crippling arthritis. The aim of the research was to determine the effect of giving red ginger compresses on reducing the pain scale in gouty arthritis sufferers at Horas Insani Hospital. This research design uses a Quasi experimental design with a one group pre-posttest design where this research is carried out by observing groups of subjects before the intervention, then observing again after the intervention. The total population for this study was all 16 gouty arthritis patients who visited Horas Insani Pematang Siantar Hospital in January – April 2023. Sampling was taken using total sampling technique. Total sampling means the number of samples is the same as the population or the entire population used as a sample is 16 people. The instruments used were observation sheets and the Numerical Rating Scale (NRS) questionnaire with the Wilcoxon test because the data distribution did not have a normal distribution, namely <0.05. The research results showed that the pain scale for gouty arthritis patients before being given the intervention was the lowest score of 4 and the highest was 6 in the moderate pain category and the pain scale after being given the intervention was the lowest score of 2 and the highest was 4 in the mild pain category. The conclusion of this study was that there was an effect of giving red ginger compresses on reducing the pain scale in gout arthritis sufferers at Horas Insani Hospital with a p value of 0.001 < 0.05. Suggestions for future researchers can develop research by controlling gout arthritis pain by providing non-pharmacological therapy such as acupressure therapy, Benson relaxation, guided imagery and others. Apart from that, future researchers can use a control group and can compare it with other aromatherapy.